Geneza komedii Piotra Cieklińskiego "Potrójny z Plauta" na tle reklam wydawniczych i panegiryków przyjaciół poety - Pirecki, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
The genesis of "Potrójny" z Plauta by Piotr Ciekliński has never before been treated as an independent subject of scientific study. This text deals with the work by Ciekliński and shows various backgrounds of it. The first one is the context of remains of letters which survived until today, the other one treats about the dedications which were printed before "Potrójny" z Plauta was first published.